Emotional dysfunctions in neurodegenerative diseases. Issue 8 (5th June 2015) - Löffler, Leonie A.K.; Radke, Sina; Morawetz, Carmen; Derntl, Birgit
ABSTRACT: Neurodegenerative diseases are characterized primarily by motor signs but are also accompanied by emotional disturbances. Because of the limited knowledge about these dysfunctions, this Review provides an overview of emotional competencies in Huntington's disease (HD), Parkinson's disease (PD), and multiple sclerosis (MS), with a focus on emotion recognition, emotion regulation, and depression. Most studies indicate facial emotion recognition deficits in HD and PD, whereas data for MS are inconsistent. On a neural level, dysfunctions of amygdala and striatum, among others, have been linked to these impairments. These dysfunctions also tap brain regions that are part of the emotion regulation network, suggesting problems in this competency, too. Research points to dysfunctional emotion regulation in MS, whereas findings for PD and HD are missing. The high prevalence of depression in all three disorders emphasizes the need for effective therapies. Research on emotional disturbances might improve treatment, thereby increasing patients' and caregivers' well‐being. J. Comp. Neurol. 524:1727–1743, 2016. © 2015 Wiley Periodicals, Inc. Abstract : Emotional disturbances such as emotion recognition deficits and depression are frequently observed in neurodegeneratives diseases such as Huntington's disease (HD), Parkinson's disease (PD), and multiple sclerosis (MS). Preliminary results further support emotional dysregulation in these diseases, underscoring the importance of more research in this field to improve patient well‐being.